2022
DOI: 10.3390/foods11040550
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis Reveals Nutritional Diversity among Three Staple Crops and Three Fruits

Abstract: More than 2 billion people worldwide are under threat of nutritional deficiency. Thus, an in-depth comprehension of the nutritional composition of staple crops and popular fruits is essential for health. Herein, we performed LC-MS-based non-targeted and targeted metabolome analyses with crops (including wheat, rice, and corn) and fruits (including grape, banana, and mango). We detected a total of 2631 compounds by using non-targeted strategy and identified more than 260 nutrients. Our work discovered species-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
(47 reference statements)
0
18
0
Order By: Relevance
“…Crops had a wide range of metabolic characteristics. We can focus on the differences to make more a sensible dietary organization to benefit human health, especially to increase the accumulation of nutrients and health benefits in grains and develop functional foods [ 16 ]. From the comparison of the content differences, we found that foxtail millet had natural advantages, with rich and unique nutritional value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crops had a wide range of metabolic characteristics. We can focus on the differences to make more a sensible dietary organization to benefit human health, especially to increase the accumulation of nutrients and health benefits in grains and develop functional foods [ 16 ]. From the comparison of the content differences, we found that foxtail millet had natural advantages, with rich and unique nutritional value.…”
Section: Discussionmentioning
confidence: 99%
“…There are relatively similar flavonoid accumulation patterns among rice, wheat and maize, compared with other non-crop species such as Arabidopsis and tobacco [ 15 ]. The accumulation of specific flavonoids also affected the different nutritional value between fruits (including grape, mango and banana) and staple food crops (including rice, wheat, and maize) [ 16 ]. Carotenoids are important phytochemicals that provide nutritional benefits to cereal products, particularly the improvement of provitamin A carotenoids, which can alleviate vitamin A deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study indicated that flavonoids act as key metabolites underlying the evolutionary disparities between maize and rice (Deng et al, 2020). Additionally, a metabolomic analysis of three staple crops (wheat, rice, corn) and three fruits (grape, banana, mango) unveiled that crop-specific metabolites primarily contain flavonoids and lipids, whereas fruit-specific nutrients are predominantly flavonoids, providing metabolic evidence for a healthy human diet (Shi et al, 2022). Despite the existence of several databases facilitating research on plant metabolism, such as the Kyoto Encyclopedia of Genes and Genomes (KEGG) (Kanehisa and Goto, 2000), Plant Reactome (Naithani et al, 2020), and Plant Metabolic Network (PMN) (Hawkins et al, 2021), there remains a notable absence of a comprehensive platform for conducting comparative analyses of intra- and cross-species metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the large-scale detection of molecular metabolite species and quantitative changes using metabolomic technology has gradually increased ( Xiong et al, 2022 , Zhan et al, 2022 ). Based on metabolomic technology, previous studies explored the metabolic processes of nutrients in crops (wheat, rice, and maize) and fruits (grapes, bananas, and mangoes) and found complementary patterns of nutrients ( Shi et al, 2022 ). In previous research, our team used metabolomic technology and found that the antioxidant capacity of purple rice was higher than that of white rice, and the flavonoids and phenol metabolites were closely related to the antioxidant capacity ( Xiong et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%